2016
DOI: 10.1093/bja/aew266
|View full text |Cite
|
Sign up to set email alerts
|

Fluid resuscitation management in patients with burns: update

Abstract: Since 1968, when Baxter and Shires developed the Parkland formula, little progress has been made in the field of fluid therapy for burn resuscitation, despite advances in haemodynamic monitoring, establishment of the 'goal-directed therapy' concept, and the development of new colloid and crystalloid solutions. Burn patients receive a larger amount of fluids in the first hours than any other trauma patients. Initial resuscitation is based on crystalloids because of the increased capillary permeability occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 79 publications
0
61
0
7
Order By: Relevance
“…29 Possibly, changes in the medical fitness of the population, with an increased incidence of diabetes and substance addiction, may also affect fluid needs. 30 In a thorough evaluation of the literature, Guilabert et al 77 performed a nonsystematic review to help determine the current evidence and recommendations for the early resuscitation of burn patients. In their review, published in the British Journal of Anaesthesiology in September 2016, they observed that many burn units based their resuscitation practices on formulas that were almost 50 years old despite the advances in hemodynamic monitoring.…”
Section: The Conundrum: Underresuscitation and Shock Versus "Fluid Crmentioning
confidence: 99%
“…29 Possibly, changes in the medical fitness of the population, with an increased incidence of diabetes and substance addiction, may also affect fluid needs. 30 In a thorough evaluation of the literature, Guilabert et al 77 performed a nonsystematic review to help determine the current evidence and recommendations for the early resuscitation of burn patients. In their review, published in the British Journal of Anaesthesiology in September 2016, they observed that many burn units based their resuscitation practices on formulas that were almost 50 years old despite the advances in hemodynamic monitoring.…”
Section: The Conundrum: Underresuscitation and Shock Versus "Fluid Crmentioning
confidence: 99%
“…The majority of burn services in England and Wales use resuscitation volumes based on the Parkland Formula of between 3 and 4mL/kg/%BSA [18]. There is still a considerable variation in fluid resuscitation protocols between services, representing a lack of consensus in how moderate sized partial thickness scalds in children should be resuscitated and very little high quality evidence is available to guide practice [24,25]. Most of the literature reporting problems with using a large volume of fluid arise from research on adult burns, but evidence is emerging that the same may be true in children.…”
Section: Resultsmentioning
confidence: 99%
“…Hipertonik solüsyonlar, albumin ve plazma, başlangıç resüsitasyon volüm gereksinimini azaltmakta, batın içi basıncın (İAB) artmamasına ve kompartman sendromu sıklığının azalmasına yol aç-maktadır. Yanık olgularında yeğlenecek solüsyonlar-dır [33] .…”
Section: Güvenlik Sorunuunclassified